Refractory and super‐refractory status epilepticus in adults: a 9‐year cohort study. (15th April 2016) - Delaj, L.; Novy, J.; Ryvlin, P.; Marchi, N. A.; Rossetti, A. O.
Abstract : Objective: While status epilepticus (SE) persisting after two antiseizure agents is called refractory (RSE), super‐refractory status epilepticus (SRSE) defines SE continuing after general anaesthesia. Its prevalence and related clinical profiles have received limited attention, and most studies were restricted to intensive care facilities. We therefore aimed at describing RSE and SRSE frequencies and identifying associated clinical variables. Methods: Between 2006 and 2015, consecutive adult SE episodes were prospectively recorded in a registry. Occurrence of RSE and SRSE and their relationship to clinical variables of interest, including outcome, were analysed. Results: Of 804 SE episodes, 268 (33.3%) were RSE and 33 (4%) SRSE. Coma induction for SE treatment occurred in 79 (9.8%) episodes. Severe consciousness impairment (OR 1.67; 95% CI 1.24–2.46; P = 0.001), increasing age (OR 1.01, 95% CI 1.01–1.02), and lack of remote symptomatic SE aetiology (OR 0.48; 95% CI 0.32–0.72) were independently associated with RSE, while severe consciousness impairment (OR 4.26; 95% CI 1.44–12.60) and younger age (OR 0.96; 95% CI 0.95–0.99) correlated with SRSE; however, most SRSE episodes were not predicted by these variables. Mortality was 15.5% overall, higher in RSE (24.5%) and SRSE (37.9%) than in non‐refractory SE (9.8%) ( P < 0.001). Significance: Super‐refractory status epilepticus appears clearly less prevalent in this cohort than previously reported, probably as it is not restricted to intensive care unit. SRSE emerges in younger patients with marked consciousness impairment, pointing to the underlying severe clinical background, but these variables do not predict most SRSE developments. There is currently a knowledge gap for prediction of SRSE occurrence that needs to be filled.